Eksperimen Modul High Temperature Composite Sebagai Material Produk Interior - Victor, Victor; Kusumarini, Yusita (Intra, 2018)
PT Pemuda Prima Usaha is a company engaged in the field of construction and engineering. The company has one of the products namely High Temperature Composite (HTC). This material has been widely applied to insulation in oil piping, but has not been applied in the field of interior. Therefore, this study aims to cultivate the development of HTC into interior materials. In addition, the potential of HTC research results will also be processed as furniture materials. After that evaluation is done to know the advantages and disadvantages of HTC. HTC material research in the form of experiments using a combination method of quantitative and qualitative methods. Quantitative method in this study are measuring the composition and strength, while the qualitative method will assess the aesthetics of the material. The result of material development in the form of new modules used as furniture material. Potential material modules in the form of furniture chairs, tables, and shelves can also be developed into several furniture. The results of the evaluation of new material testing are yellow, waterproof, heat-resistant, finishing, screw-able, and non-UV resistant.